1982
DOI: 10.1136/bjo.66.5.280
|View full text |Cite
|
Sign up to set email alerts
|

HLA antigens and other risk factors in the development of retinopathy in type 1 diabetes.

Abstract: SUMMARY Factors possibly influencing the development of diabetic retinopathy were studied in 112 randomly selected type I diabetics having no or minimal retinopathy (group A) and in 82 type 1 diabetics with known severe diabetic retinopathy. The latter comprised those with severe background retinopathy (group B, n= 17) and those having proliferative retinopathy without (group C, n=38) and with (group D, n=27) diabetic nephropathy. Nonretinopaths (group A) were of similar sex ratio, body weight, and age at diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…This result was supported by many earlier studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), but not by others (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In the younger-onset group, there was some suggestion of a relationship between smoking and the incidence of any retinopathy in both univariate and multivariate analyses, but it was weak.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…This result was supported by many earlier studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), but not by others (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In the younger-onset group, there was some suggestion of a relationship between smoking and the incidence of any retinopathy in both univariate and multivariate analyses, but it was weak.…”
Section: Discussionsupporting
confidence: 45%
“…Cigarette smoking, a characteristic with potential for modification, if proved to be a risk factor for retinopathy, would have great public health implications for the prevention of this complication. Some studies have found an association between cigarette smoking and diabetic retinopathy (3)(4)(5)(6)(7)(8)(9)(10)(11)(12), whereas others have not (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Many of these studies are hampered by their cross-sectional design or small sample sizes.…”
mentioning
confidence: 93%
“…Specifically, no relation has been found between IAs and histological findings of nephropathy (331), muscle basement membrane thickness (332), clinical nephropathy (114, 333,334), clinical retinopathy (114, 273,[321][322][323][332][333][334][335][336], clinical autonomic neuropathy (337), clinical peripheral neuropathy (338), or complement activation in patients with diabetes (339).…”
Section: F Immune Complexesmentioning
confidence: 99%
“…The results of these studies have been inconsistent as some reported an association between B8 and proliferative retinopathy (4,5), others found an association with B15 (6)(7)(8)(9), and others reported no HLA-B antigen associations (10)(11)(12)(13)(14)(15)(16)(17). With the advent of DR typing, attention shifted to these antigens, partly because of their stronger associations with IDDM development.…”
mentioning
confidence: 94%